[Death penalty ; This side of paradise ; Southern winds [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles death penalty; Boracay's garbage problem, land and water pollution and drugs; and Mike de Leon's film which was included in an anthology produced for the 25th anniversary of the ASEAN.